(3QSGdI aj JbGSje GdMceIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3gPg QSGdI ai JbGSje GdMceI ddTjN GdQFjS CHj Ydi Hf YHO Gddg Hf SjfG bGd GdMeO ddg edge GdUhGH hefhQ GdCdHGH hhGgH GdYbd hGdeJcad HGdYOd hHYO abO EdJeSJ efi Cf CTjQ Edi CbSGe GdYdhe GdYbdjI s
(3BNQgG (B:s
(3dCf GdUfGYI faSgG JhLgg hdfNJe ebGdJfG gPg HGdMeO dhGgH GdYbd hGdJhajb hGdYUeI hMSHfG Gddg hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B((3eLGejY (B11(2)) s
Keywords: (3GdadSaI hGdefWbs